Analytical method for fast tuning of a PID compensator for first and second order plants with dead time - ílvarez Arocha, César Francisco (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
The following article presents an analytical method for a fast calculation of constants of a PID compensator using the step response of first or second order plants with dead time, This method allows us to obtain the proper constants of the PID compensator before of the stabilization of !he system output response. lt means time savings in the tuning of the controller. On the other hand, the tuning algorithm is easy to implement, because the equations obtained can be aproximated by third degree polinomials. Finally, the simulated response graphics of some feedback systems, which use the tuning algorithm proposed, are shown. The responses obtained, have very good characteristics of stability, accuracy and speed, in plants with different values of time constants.